The Growth Performance of Oil Palm Seedlings in Pre-Nursery and Main Nursery Stages as a Response to the Substitution of NPK Compound Fertilizer and Organic Fertilizer - Adileksana, Cahyo; Yudono, Prapto; Purwanto, Benito Heru; Wijoyo, Rachmanto Bambang (Caraka Tani: Journal of Sustainable Agriculture, 2020)
The need of nitrogen (N), phosphate (P) and potassium (K) nutrient in oil palm nursery are usually fulfilled with synthetic chemical fertilizers such as NPK fertilizer. The application of NPK fertilizer can cause the soil to become hard due to the accumulation of the residue left on the ground. Cow manure is able to substitute NPK fertilizer based on the chemical status of the soil. This study aimed at analyzing the effect of NPK fertilizer substitution with cow manure on the growth of oil palm seedlings in the pre-nurseries and main nurseries. The experiment was conducted from February to September 2018 in the Banguntapan research and experimental field, Faculty of Agriculture, Universitas Gadjah Mada. The experiment applied the Randomized Complete Block Design (RCBD) with one factor and six blocks as replications. The factors were subtitution using the replacement series method with five levels of doses, 100% NPK, 75% NPK + 25% cow manure, 50% NPK + 50% cow manure, 25% NPK + 75% cow manure and 100% cow manure. The observed parameter variables were root lenght, root area, hump diameter, leaf area, the number of leaves, plant height and plant dry matter. The use of 25% NPK substitute with 75% organic material was the best result in increasing the growth performance of oil palm seddlings in pre-nursery and main nursery.